Social bonds predict dominance trajectories in adult male chimpanzees. (September 2021) - Bray, Joel; Feldblum, Joseph T.; Gilby, Ian C.
Abstract : In some species, individuals form well-differentiated and affiliative social relationships that facilitate cooperation and confer adaptive benefits, but few studies of males have addressed the benefits of same-sex social bonds. Among mammals, adult male chimpanzees, Pan troglodytes, form some of the strongest and most stable social bonds, and several studies have found that higher-ranking males attain short- and long-term benefits. No study in chimpanzees, however, has demonstrated a link between social bonds and dominance trajectories. To fill this gap, we used 37 years of data from Gombe National Park, Tanzania, to test the hypothesis that social bonds in adult male chimpanzees predict changes in dominance strength, which were measured by annual changes in mean Elo scores. Across 24 adult males, we found that social bonds, which were identified using both association in small groups and grooming activity, showed positive relationships with changes in dominance strength. From previous studies, the most likely mechanism for the observed relationship between adult male bond strength and dominance trajectories is the formation of cooperative coalitions, by which males with stronger bonds leverage established relationships to maintain or increase their position in the dominance hierarchy. Given the fission–fusion social structure of chimpanzees, both party-level associations and grooming relationships are essential components of male social bonding, and these results, in combination with prior studies, suggest that having strong social bonds is a valuable strategy for achieving higher rank. Highlights: Some species form social bonds that facilitate cooperation and provide benefits. Adult male chimpanzees form some of the strongest and most stable social bonds. No study in chimpanzees has found a link between bonds and dominance trajectories. Social bonds were positively associated with changes in dominance strength. Multiple mechanisms may link higher rank and increased fitness.